(untitled) (Global Journal of Human-Social Science, 2015)
English has currently been spoken all over the world, which substantially influences its development. In Bangladesh, English is taught at all levels of education. Moreover, it has become a notion that if a person does have a good command of English, that person is going to get a very good job. To learn English, a learner has to go under a complex process of committing errors. This paper is meant to present how the English variety in Bangladesh has been phonologically and grammatically written and spoken full of errors. This paper reviews errors on grammatical, lexical, and phonological aspects of written and spoken English with theoretical background and procedure of error analysis. It empirically through qualitative and quantitative method finds out the errors in pronunciation, grammar, articles, auxiliaries, and prepositions and also reflects the possible reasons behind the errors in written and spoken English. Finally, it provides some recommendations for effective remedial measures and feedback techniques for developing spoken English in the light of the theoretical and empirical findings of the research.